2016
DOI: 10.5664/jcsm.5406
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression among Untreated Obstructive Sleep Apnea Patients Using a Standardized Psychiatric Interview

Abstract: Study Objectives: The aims of this study were: (1) to use a standardized psychiatric interview, conducted by a trained psychologist to assess the prevalence of depression among patients with untreated OSA, and (2) to identify if OSA severity or other comorbid disorders (insomnia, hypertension, and diabetes) are related to depression among patients with untreated OSA. Methods: Participants were newly diagnosed patients with OSA (n = 284) waiting to start positive airway pressure (PAP) treatment. The Mini Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 36 publications
8
43
0
Order By: Relevance
“…The main finding is consistent with studies reporting an increased incidence of OSA symptoms in patients with depression, building a long-standing co-occurrence of mood and sleep disorders (11,24). The results are also consistent with studies indicating that untreated OSA patients might show higher depressive symptoms (38)(39)(40). Several studies have shown that existence of treatment resistant symptoms in patients with OSA might be due to depression and not due to OSA per se (41)(42)(43).…”
Section: Discussionsupporting
confidence: 81%
“…The main finding is consistent with studies reporting an increased incidence of OSA symptoms in patients with depression, building a long-standing co-occurrence of mood and sleep disorders (11,24). The results are also consistent with studies indicating that untreated OSA patients might show higher depressive symptoms (38)(39)(40). Several studies have shown that existence of treatment resistant symptoms in patients with OSA might be due to depression and not due to OSA per se (41)(42)(43).…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have produced conflicting results regarding the association between OSA severity and mental disorders (Bahammam et al ., ). In an Icelandic study (Bjornsdottir et al ., ), no association was found between AHI or oxygen desaturation index and depression diagnosed with the Mini International Neuropsychiatric Interview. Similarly, an American study did not find any association between OSA severity and depression or anxiety when assessing the two latter constructs with the Beck Depression Inventory and the Beck Anxiety Inventory, respectively (Macey et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, several other studies have failed to find an association between OSA severity and the prevalence of depression and anxiety (Bjornsdottir et al ., ; Douglas et al ., ; Macey et al ., ). A methodological limitation of the aforementioned studies is that they were based on small samples, ranging from 49 to 426 participants (Bjornsdottir et al ., ; Douglas et al ., ; Edwards et al ., ; Macey et al ., ). Furthermore, in a study among 825 elderly people (aged ≥ 65 years), neither the presence nor the severity of OSA were associated significantly with depression or anxiety.…”
Section: Introductionmentioning
confidence: 98%
“…Patients with co‐morbid OSA and insomnia may have more alterations in nocturnal sleep but do not have a greater cardiovascular risk than patients with OSA alone . Co‐morbid OSA and insomnia patients do consistently report higher rates of psychiatric disorders, anxiety and depression than OSA patients without insomnia in sleep clinic studies . In contrast, a large retrospective case–control study of ambulatory databases based on healthcare visits to physicians and hospital departments in the United States found no association between co‐morbid OSA and insomnia and physician‐rated psychiatric syndromes .…”
Section: Introductionmentioning
confidence: 95%